Health econometrics - Baltagi, Badi H. (Badi Hani); Moscone, Francesco (Bingley, U.K. : Emerald Publishing Limited, 2018)
Recent years have witnessed a dramatic surge in applied econometric work in health economics, enhanced by the availability of large micro and macro data sets as well as the rapid development of new techniques and tools in econometrics. Health economics is an important and challenging area of research for applied econometricians, due to complexity embedded in the data, arising from issues such as nonlinearity of models, the presence of individual-level unobserved heterogeneity as well as time and cross sectional dependencies.This book covers a wide range of existing and emerging topics in applied health economics. These include: behavioural economics, medical care risk, social insurance, discrete choice models, cost-effectiveness analysis, health and immigration, vignette approach, response of parental investments to childs health at birth, determinants of innovation in the pharmaceutical industry, hospital competition, use of administrative data, spatial health econometrics, health expenditure, and networks.
Prelims -- Experimental methods and behavioral insights in health economics: estimating risk and time preferences in health -- Subjective expectations of medical expenditures and insurance in rural Ethiopia -- Social insurance and health -- Discrete choice methods in health economics -- Migration, health, and well-being: models and methods -- Econometric considerations when using the net benefit regression framework to conduct cost-effectiveness analysis -- Anchoring vignettes and cross-country comparability: an empirical assessment of self-reported mobility -- Response of parental investments to childs health endowment at birth -- R&D success in pharmaceutical markets: a duration model approach -- Medical malpractice: how legal liability affects medical decisions -- Hospital economics: the effect of competition, tariffs and non-profit status on quality -- Administrative data and health outcome assessment: methodology and application -- Spatial health econometrics -- Cross-country medical expenditure modeling using OECD panel data and ARDL approach: investigating GDP, technology, and aging effects -- Large network inference: new insights in health economics -- About the volume editors -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Econometrics; Medical economics; Business & Economics -- General; Economics, finance, business & management